PROMOSI PROMOSI PROMOSI OBJEK OBJEK WISATA WISATA WISATA WISATA WISATA WISATA TAMAN HUTAN RAYA SULTAN SYARIF TAMAN HUTAN RAYA SULTAN SYARIF TAMAN HUTAN RAYA SULTAN SYARIF TAMAN HUTAN RAYA SULTAN SYARIF TAMAN HUTAN RAYA SULTAN SYARIF TAMAN HUTAN RAYA SULTA - Adelina Tampubolon; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this study was to determine the response of respondents to the promotion of the implementation of the Forest Park attractions Sultan Syarif Hasyim II by using the promotional mix consists of advertising, sales promotion, personal selling and public relations. This study uses the theory Yoeti ( 1996:186 ).This theory divides the promotion mix with 4 categories of advertising , sales promotion, personal selling and public relations. These four kinds of activities is a common communication commonly used, but for the purpose wide in order to influence the thoughts and behavior of people.The method used is descriptive qualitative authors describe and explain in detail about the issues that will be examined based on the data that has been previously obtained from a questionnaire study report / questionnaire that has been collected , analyzed and then after it is spoken in the form of sentences and then drawn a conclusion. Ruslan ( 2003:193 ).The results of this study is that the implementation of the campaign carried Tahura good manager in advertising, sales promotion, personal selling and public relations are not satisfactory in promoting tourist attraction. These results are summarized on the summary and questionnaire answers. Companies to be more creative in making promotions to attract a lot of people come to visit the Forest Park Sultan Syarif Hasyim II .Keywords: promotion, respondent’s response to promotion mix (advertising, sales promotion,personal selling, and public relation)